Enhanced Carbon Capture Behavior of Carbon Fibers via Ionic Liquid Modification. Issue 1 (17th November 2022) - Mokhtari‐Nori, Narges; Luo, Huimin; Paul, Ryan; Vautard, Frederic; Fu, Yuqing; Fan, Juntian; Jiang, De‐en; Yang, Zhenzhen; Dai, Sheng
Abstract: Carbon‐based materials are widely deployed in carbon capture but are only limited to physisorption procedures. Further extending functionalized carbon materials to CO2 chemisorption under low CO2 concentration is highly desirable yet challenging. Herein, a carbon fiber composed of solely ultra‐micropores (∼0.45 nm) was deployed as the precursor to avoid the pore blocking effect, which was modified by superbase‐derived ionic liquids (ILs) containing strong interaction sites with CO2 . By forming a thin coating layer on the surface, the as‐afforded surface‐functionalized fiber materials demonstrated enhanced CO2 uptake capacity and improved CO2 sorption kinetics, as evaluated by both the volumetric method and thermogravimetric analysis, as well as the calculated energy distribution curves. The achievements made in this work provide guidance on the functionalization of carbon‐based materials towards enhanced CO2 chemisorption by forming a thin layer of selected IL coating. Abstract : A surface modification pathway was developed to tune the CO2 chemisorption behavior of carbon materials. Without the influence of porosity blocking, enhanced carbon capture was achieved by coating the carbon fibers containing ultra‐micropores with superbase‐derived ionic liquid, being evaluated by the volumetric pressure‐swing procedure and thermogravimetric analysis method and demonstrating the combined merits of solid and liquid sorbents.